Depression, self‐esteem and sexual function in laryngeal cancer patients. (August 2015) - Yılmaz, M.; Yener, M.; Yollu, U.; Akil, F.; Haciyev, Y.; Yargic, I.; Karaman, E.; Cansiz, H.
<x xml:space="preserve">Abstract</x> Objective The purpose of this study was to assess sexual function, affective disorders and self‐esteem in patients who were surgically treated for laryngeal cancer. Design Retrospective, blind, cross‐sectional study. Setting Single tertiary cancer centre. Participants Seventy four patients who were operated on Istanbul University Cerrahpasa School of Medicine Otorhinolaryngology Department between 2008 and 2012 were classified according to the type of the operation as total laryngectomy (Group 1) and partial laryngectomy (Group 2). Main outcome measures Sexual dysfunction, depression and self‐esteem were evaluated with The Arizona Sexual Experiences Scale (ASEX), Beck's Depression Inventory (BDI) and Rosenberg Self‐Esteem Scale (RSES), respectively. Results Average ASEX scores of the Group 1 were (13.98 ± 6.32) and Group 2 were (13.08 ± 4.96) without statistically significant difference (P = 0.537). Mean BDI score of Group 1 was (13.20 ± 10.41) higher than Group 2 (7.76 ± 8.14) and the difference was significant statistically (P = 0.026). Mean RSES scores of Group 1 and Group 2 were 20.68 ± 5.33 and 19.25 ± 4.70, respectively, again without significant difference (P = 0.262). However, when the average scores of each item of Rosenberg Scale were compared, significant difference was found in d4 (2.37 ± 0.78; 1.64 ± 0.99; P = 0.001), d6 (1.22 ± 1.05; 1.84 ± 1.14; P = 0.023), d10 (2.55 ± 2.39; 1.28 ± 1.49; P = 0.018) and d11 (1.35 ± 0.95; 2.00 ± 1.41; P = 0.021). BDI scores were correlated with RSES scores, and ASEX scores were correlated with age. Conclusion The patients with total laryngectomy seem to have more psychological problems that must be addressed in the postoperative period.